Documentaries as Multimodal Texts to Promote Reading in the Virtual Language Classroom: An Experimental Study - N.W.S.C Wijewantha (Journal of English Language Teaching and Linguistics, 2021)
As education today is immensely reliant on distant and virtual learning methods, addressing the individual learning styles of the students is a challenging task particularly in second language teaching. Therefore, this study examines the use of documentaries as multimodal texts in the virtual language classroom to promote reading. 50 first year undergraduates enrolled in the BSc. degree program at a Sri Lankan national university were selected for the study and they were randomly divided into two groups; experimental and control. The virtual application used in the study was Google Classroom and a subtitled documentary was shared among the students of experimental group whereas the controlled group was given access to the transcript of the same documentary. After allocating adequate reading time for both groups, a test paper was simultaneously assigned using the same platform. While the students’ scores were analyzed to evaluate the effectiveness of the two reading approaches, a questionnaire was virtually distributed among the participants of the experimental group to gather their perspective on the use of documentary. The findings revealed that, using documentaries as digital multimodal texts is a successful language acquisition method which enhances the students’ comprehension and enthusiasm in learning the language. Further, using documentary was identified as a novel experience in the virtual classroom. Hence, the study recommends the incorporation of digital texts in virtual language teaching as a multimodal approach.